Radioactive lead studies in the human - Blake, Keith Charles Hughes (Division of Medical Physics, 2018)
The differing susceptibility of individuals to the toxic effects of chronic lead exposure has never been fully understood. As the major intake of lead in the human is from food and beverages, any variation between individuals of the quantity of lead absorbed from the gut, and of the distribution and excretion of this lead, may account for the differences in individual susceptibility. The food and beverages themselves may have an influence, and to investigate their effects on absorption, distribution and excretion of lead, experiments were performed on normal subjects using a short-lived radionuclide of lead, ²⁰³Pb, and instruments generally available in Nuclear Medicine. Lead absorption between different individuals showed a wide variation when ²⁰³Pb was taken as a single dose between meals. The effect of fasting was to increase absorption and reduce the variation. This suggested that food with the lead in the gut was mainly responsible for the variation in lead absorption between individuals. This was confirmed when ²⁰³Pb was mixed into a control meal and eaten by fasted subjects. Lead absorption was again low and variable. In contrast, ²⁰³Pb taken in distilled water was avidly absorbed with little variation between subjects. The absorption of lead in water could be appreciably more than lead in food amongst the general population. Minerals were found to be mainly responsible for affecting absorption when one subject ingested ²⁰³Pb in control meals from which one dietary constituent at a time was omitted. The effect of minerals in reducing absorption of lead was greatest when they were ingested in distilled water. Lead in water with a low mineral content, such as 'soft' water, could be a hazard to population groups living in 'soft' water areas. There were also indications from these experiments that dietary constituents may affect the distribution and excretion of lead. Calcium and phosphorous were found to reduce the absorption of ²⁰³Pb to approximately the same level as that produced by the total minerals. Calcium reduced absorption more than phosphorous when these minerals were ingested separately with ²⁰³Pb. Paired kinetic experiments showed that calcium and phosphorous ingested at the same time as ²⁰³Pb affected its distribution in the body but not its rate of excretion. Using the data from the kinetic experiments, a compartmental model was developed which adequately described the kinetics of orally ingested ²⁰³Pb. The model suggested that calcium is mainly responsible for reducing absorption of lead from the gut, but that the effect of phosphorous is to increase soft tissue levels of lead at the expense of red cell lead. As susceptibility is related to soft tissue levels of lead, this suggests that the 'protective' effect of calcium in the gut is reduced. This could not be confirmed, however, as the kinetic data were insufficient for the model to distinguish the tissues particularly vulnerable to lead toxicity in the soft tissue compartment. It was concluded that the calcium and phosphorous in the diet could influence susceptibility to lead toxicity through changes in the absorption of food and water lead and in the distribution of lead in the body. The results suggest that the prophylactic effect of calcium on lead absorption should be recognised and applied in this time of increased environmental levels of lead.